Neo-liberalism, Crisis and the Contradictions of Depoliticisation - Burnham, Peter (PARTECIPAZIONE E CONFLITTO, 2017)
This paper develops a political economy analysis of depoliticisation in the context of the crisis of neo-liberalism in Western Europe. Following a discussion of the theoretical foundations of the concept, it emphases that whilst depoliticisation strategies are often associated with neo-liberalism, such strategies have a longer trajectory existing even within Keynesian regimes. The paper then details the many forms taken by depoliticisation within neo-liberal governing regimes focusing on the reorganisation of civil society and the state from the late 1970s to the present primarily with examples from the UK. It suggests, contrary to much popular discussion, that there is a significant degree of continuity in the form of economic manage-ment followed before, during and after the recent financial crisis of 2008/09. Both in terms of ideology and practice, many governments have maintained and even deepened their commitment to depoliticised gov-erning principles. However it seems clear that attempts to depoliticise neo-liberal economic policy have not enabled state managers to avoid the emergence of crisis at the level of the state. Contrary to accounts which argue in simplistic fashion that `economic’ crisis produces `political’ crisis, this paper suggests that crisis is best understood as expressed simultaneously in both economic and political forms. Crisis at the level of the state precipitated in part by the entrenchment of depoliticised governing strategies is not simply the result of economic crisis but is an aspect of that crisis contributing to its depth and apparent insolubility. In this way the paper challenges some critiques of depoliticisation which have suggested (Hay 2014, 303) that the concept is in part both fatalistic and functionalist removing much of the political contingency of the moment of crisis itself.